Analisis Keresahan Masyarakat di Lingkungan Desa Laut Dendang, Dusun VI dalam Membuang Sampah di Jalanan : Studi Kasus - Candra Kirana; Iin Natasya Divana Ginting; Muhammad Abdillah; Nirina Triazi; Sari Wulandari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Environmental contamination in Laut Dendang Village, Hamlet VI is caused by the community's acts of discarding waste. The purpose of this research is to examine the worries of the locals in Laut Dendang Village, Hamlet VI, over the careless littering of the streets by some residents. Because people are becoming more aware of the environmental difficulties caused by littering and the dangers it poses to both humans and other forms of life. Community members were interviewed and observed using socialisation methods as part of this study's quantitative and qualitative descriptive methodology. Ten members of the Laut Dendang Village community in Hamlet VI served as study subjects for this activity, which took place in the Laut Dendang Village setting. It is clear from the interview data that people in Laut Dendang Village remain worry about littering the streets with plastic trash since they don't know the consequences of doing so. Even when people have a good grasp of the topic, it doesn't mean they're aware of the need to prevent river pollution.